Chemical speciation of environmentally significant metals with inorganic ligands. Part 5: The Zn 2+ + OH - , Cl - , CO 3 2- , SO 4 2- , and PO 4 3- systems (IUPAC Technical Report) - Powell, Kipton J.; Brown, Paul L.; Byrne, Robert H.; Gajda, Tamás; Hefter, Glenn; Leuz, Ann-Kathrin; Sjöberg, Staffan; Wanner, Hans (Pure and applied chemistry, 2013)
The numerical modeling of Zn II speciation amongst the environmental inorganic ligands Cl - , OH - , CO 3 2- , SO 4 2- , and PO 4 3- requires reliable values for the relevant stability (formation) constants. This paper compiles and provides a critical review of these constants and related thermodynamic data. It recommends values of log 10 β p,q,r ° valid at I m = 0 mol·kg -1 and 25 °C (298.15 K), and reports the empirical reaction ion interaction coefficients, ∆ ε , required to calculate log 10 β p,q,r values at higher ionic strengths using the Brønsted-Guggenheim-Scatchard specific ion interaction theory (SIT). Values for the corresponding reaction enthalpies, ∆ r H , are reported where available. There is scope for additional high-quality measurements for the Zn 2+ + H + + CO 3 2- system and for the Zn 2+ + OH - and Zn 2+ + SO 4 2- systems at I > 0. In acidic and weakly alkaline fresh water systems (pH < 8), in the absence of organic ligands (e.g., humic substances), Zn II speciation is dominated by Zn 2+ (aq). In this respect, Zn II contrasts with Cu II and Pb II (the subjects of earlier reviews in this series) for which carbonato- and hydroxido- complex formation become important at pH > 7. The speciation of Zn II is dominated by ZnCO 3 (aq) only at pH > 8.4. In seawater systems, the speciation at pH = 8.2 is dominated by Zn 2+ (aq) with ZnCl + , Zn(Cl) 2 (aq), ZnCO 3 (aq), and ZnSO 4 (aq) as minor species. This behaviour contrasts with that for Cu II and Pb II for which at the pH of seawater in equilibrium with the atmosphere at 25 °C (log 10 {[H + ]/ c °} ≈ 8.2) the MCO 3 (aq) complex dominates over the MCl n (2- n )+ species. The lower stability of the different complexes of Zn II compared with those of Cu II , Pb II , and Cd II is also illustrated by the percentage of uncomplexed M 2+ in seawater, which is ca. 55, 3, 2, and 3.3 % of [M II ] T , respectively.